A CYCLONIC EDDY NORTH OF LOMBOK - Cresswell, George (Marine Research in Indonesia, 1995)
A satellite drifter that passed from south to north through Lombok Strait in early 1988 became trapped in a cyclonic eddy 100 km north of Lombok. The eddy, which was 130 km by 80 km, had a rotation period of 10 days.